Women: still the key to food and nutrition security - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The 1995 Beijing Platform for Action set goals for empowering women in developing nations. Over the five years since the Beijing +5 review assessed progress toward these goals, the International Food Policy Research Institute (IFPRI) has generated new studies reaffirming that empowering women is the key to ensuring food and nutrition security in the developing world. This brief brings together IFPRI’s most recent research findings on gender and food security and offers proof to policymakers that reducing gender disparities promotes better food and nutrition security for all....IFPRI's research findings provide empirical evidence that empowering women leads to greater household food and nutrition security. Accomplishing this task requires policies that eradicate gender discrimination, proactively promote catch-up for women, and involve women directly in their implementation..